Aplicação de Plasma Electrolytic Oxidation (PEO) para síntese de óxidos anódicos sobre alumínio em eletrólito contendo íons Ag+ - Rodrigues, Andressa (2020)
The growing concern with the quality of food by consumers, has led the industry to new technologies to guarantee this condition. Antimicrobial films appear as active packaging that, in addition to protecting and conditioning the product, also provides an extra barrier against microbiological agents through substances incorporated in the packaging. In this work, the plasma electrolytic oxidation (PEO) technique was used to produce oxide coatings on aluminum metallic substrate, whose characteristics of being a light, resistant, low-cost and recyclable metal, make it widely used in food packaging industry. In the PEO process, the metal is oxidized in a high electric field, reaching the potential for rupture of the oxide, and complex physical and chemical phenomena are observed on the surface of the substrate. This treatment is capable of promoting changes in the oxide film, improving their mechanical properties and resistance to corrosion. The anodization process was performed in galvanostatic mode, with a current density of 20 mA⁄cm², and an alkaline electrolyte of 0.1 mol.L-1 sodium silicate. In addition, ionic silver (AgNO3 1 mmol.L-1) was added to the electrolyte, due to its bactericidal property already known in the literature, and Ag particles are incorporated into the coating giving it the property of an antimicrobial film. Oxides were synthesized at different anodizing times (20 and 60 minutes), and the Scanning Electron Microscopy (SEM) technique coupled with the Dispersive Energy Spectroscopy (EDS) technique revealed that a greater amount of Ag in the oxide film was achieved in a shorter treatment time, it was also possible to observe Ag particles deposited on the oxide surface in this condition. The RBS analysis confirmed the large amount of Ag present on the sample surface prepared in a shorter treatment time (S20Ag), as well as the presence of Oxygen on the surface due to the presence of aluminum oxide in all samples. The morphology of the films revealed a porous structure, and the profilometry analysis showed that the roughness of the films increases with the treatment time. In addition, the X-ray analysis revealed the presence of the γ-Al2O3 crystallographic phase and the Infrared Spectroscopy (FTIR) analysis revealed the presence of Al-O, Si-O, Si-Al-O, and OH bonds. Finally, the bactericidal test carried out with the bacterium S. Aureus showed that coatings produced in a longer treatment time, regardless of the presence of Ag, resulted in greater inhibition (~ 85%), and for less treatment time the presence of Ag increased up to 6 times the antimicrobial activity of the coating when compared to the coating without Ag.